Z historii niepełnosprawności (XVI–XIX w.) - Kulbaka, Jacek (Biuletyn Historii Wychowania, 2018)
The article presents various circumstances (social, legal, philosophical and scientific) connected with the care, upbringing and education of people with disabilities from the early modern era to the beginning of the 20th century. Particular attention was to the history of people with disabilities in the Polish  lands. The author tried to recall the activity of leading educational activists, pedagogues and scientists – animators of special education in Poland, Europe and the world. The text also contains information related to the activities of educational and upbringing institutions (institutional, organisational, methodological and other aspects).